Faktor-Faktor Yang Berhubungan Dengan Kepuasan Pasien Rawat Jalan di Puskesmas Delitua Kabupaten Deli Serdang Tahun 2021 - Miftahul Jannah (Jurnal Rumpun Ilmu Kesehatan, 2021)
Health efforts are carried out with an emphasis on the wider community in order to achieve optimal levels of health, without neglecting the quality of service to individuals. This study aims to determine the level of satisfaction felt by patients who come for treatment regarding comfort, staff service, service procedures and also service results at the Delitua Community Health Center, Deli Serdang Regency. This research used a cross sectional study test design with a sample size of 33 people determined through saturated sampling by conducting interviews using a questionnaire. The results of the study showed that all the variables studied showed a significant relationship with patient satisfaction at the Delitua health center, namely comfort p(0.009)<a(0.05), staff service p(0.023)<a(0.05), service procedures p (0.015)<a(0.05) and service results p(0.023)(0.05), the community health center must further improve the quality of health services which include comfort, staff service, service procedures and service results, in order to provide satisfaction for patients who use them. health services at the Delitua community health center.